BABY DENTISTRY: Attention Pattem in Public Hea1th-Perú (lst part ) - Guillen Borda, Celso (2004)
Baby dentistry began in 1985 as a collaborative e!fort between the Un ivers it y of Londrina and FINEP, in response of world tendency to provide oral health a ttelltion for infallts and toddlers. , promoting educative and preventillg programs. Then, due to the successful results, public and private sector in Brazil adopted this concept . In Peru, tliere has been created the baby dentistry department in Instituto Especializado de Salud del Niño in September 1997, formed as part of a group of dental specialties in the hospital, mainly intended to provide oral health to children under 3 years old. In Peru as in many Latin-American countries, it lOas assumed that the First dental visit SllOllld start by 2 or 3 years oflife but according to some data reported in 1987 by Walter et al , tlzere lOas a high prevalen ce of dental caries in children betlOeen O and 30 months (34%). These results were coincident with otlzer works around the world. Therefore, most of the children under 3 years old could not have access to dental care, in spite of requirement of restorative treatment detected in the first visito In order to face this reality , the IESN has created baby dentistry department to provide early dental care to children under 3 years old. Patients are classified in two groups: those Who have not developed the disease , based upon the risk factors, and those who have developed the disease based in tile caries activity. Based in our experience and research, we show to the pediatric dentistry community a clinical pattern that can lead our work with this group of children.